Physiological Responses During High-Intensity Interval Training in Young Swimmers - Almeida, Tiago André Freire; Pessôa Filho, Dalton Müller; Espada, Mário Cunha; Reis, Joana Filipa; Sancassani, Andrei; Massini, Danilo Alexandre; Santos, Fernando Jorge; Alves, Francisco Besone (Frontiers in Physiology, 2021)
This study analyzed whether 100 and 200-m interval training (IT) in swimming differed regarding the temporal, perceptual, and physiological responses. The IT was performed at maximal aerobic velocity (MAV) until exhaustion and time spent near to maximal V̇O2 (V̇O2peak), total time-limit (tLim), [La-]peak, V̇O2 kinetics (V̇O2K), and rate of perceived exertion (RPE) were compared between protocols. Twelve swimmers (7 male 16.1±1.1 and 5 female 14.2±1.0 years) completed a discontinuous incremental step-test for second ventilatory threshold (VT₂), V̇O2peak, and MAV assessment. The swimmers subsequently completed two IT protocols at MAV with 100 and 200-m bouts to determine the maximal V̇O2 (Peak-V̇O2) and time spent ≥VT₂, 90 % and 95 % of V̇O2peak for the entire protocols (IT100 and IT200) and during the first 800-m of each protocol (IT8x100 and IT4x200). A portable apparatus (K4b2) sampled gas exchange through a snorkel, and an underwater led signal controlled the velocity. RPE was also recorded. The Peak-V̇O2 attained during IT8x100 and IT4x200 (57.3±4.9 vs. 57.2±4.6 ml·kg-1·min-1) were not different between protocols (p=0.98) nor to V̇O2peak (59.2±4.2 ml·kg-1·min-1, p=0.37). The time-constant of V̇O2K (24.9±8.4 vs. 25.1±6.3-s, p=0.67) and [La-]peak (7.9±3.4 and 8.7±1.5 mmol·L-1, p=0.15) also did not differ between IT100 and IT200. The time spent ≥VT2, 90 % and 95%V̇O2peak were also not different between IT8x100 and IT4x200 (p=0.93, =0.63 and =1.00, respectively). The RPE for IT8x100 was lower than IT4x200 (7.62±2.0 vs. 9.5±0.7, p=0.01). Both protocols are considered suitable for aerobic power enhancement since V̇O2peak was attained with similar V̇O2K and sustained with no differences in tLim. However, the fact that only the RPE differed between the IT protocols, suggested that coaches should consider that nx100-m/15-s is perceived as less difficult to perform than nx200-m/30-s for the first 800-m when managing the best strategy to be implemented for aerobic power training.